Pengaruh Film Penyalin Cahaya terhadap Tingkat Kesadaran Kekerasan Seksual di Kalangan Mahasiswa Fikom Unisba 2018 - Fadhila Nur Syahida; Aziz Taufik Hirzi (Bandung Conference Series: Journalism, 2023)
Abstract. Sexual violence is a form that isnot only limited to physical treatment, butalso verbal and symbolic. There are 3 factors that trigger this, namely, biological,social and cultural factors, and powerrelations. Cases of sexual violence inuniversities are increasing every year. In themidst of a cultural crush that is still thick,matters relating to sexuality are still considered taboo, this makes the victim feelreluctant to speak up. Through this film, theCahaya Cahaya film opens taboos createdfrom myths and cultures that have been firmly held by society. This study aims todetermine the effect of the film PengalinCahaya on the level of awareness of sexualviolence among students of Fikom Unisba2018. The method used is quantitative, thepopulation in this study is students ofFikom Unisba 2018 and samples taken asmany as 198 respondents using non-probability sampling technique. To determine the prospective respondents, the writer uses saturated sampling. The data analysis technique used is descriptiveanalysis, method of successive interval(MSI), normality test, simple regression analysis, t test and the coefficient of determination. After conducting research on each variable, the respondents gave a positive response that the film PengalinCahaya has a significant influence on the level of awareness of sexual violence that the variance that occurs in the Level of Awareness of Sexual Violence among students of Fikom Unisba 2018 (Y) is 69.722% determined by the variance occursin the influence variable of the LightCopying film (X). As much as 30.278% isdetermined by other factors outside thestudy. Abstrak. Kekerasan seksual merupakanbentuk yang tidak hanya sebatas perlakuanfisik, melainkan juga verbal dan simbolik.Terdapat 3 faktor yang memicu terjadinyahal tersebut yaitu, faktor biologis, sosialdan budaya, serta relasi kuasa. Kasuskekerasan seksual di perguruan tinggimeningkat setiap tahunnya. Di tengahhimpitan budaya yang masih kental, hal-halyang menyangkut seksualitas dianggapmasih tabu, hal ini membuat korban merasaenggan untuk bersuara, melalui filmPenyalin Cahaya ini membuka hal tabuyang tercipta dari mitos dan budaya yangselama ini dipegang teguh masyarakat.Penelitian ini bertujuan untuk mengetahuipengaruh film Penyalin Cahaya terhadaptingkat kesadaran kekerasan seksual dikalangan mahasiswa Fikom Unisba 2018. Metode yang digunakan kuantitatif, populasi dalam penelitian ini adalahmahasiswa Fikom Unisba 2018 dan sampelyang diambil sebanyak 198 respondendengan menggunakan teknik nonprobability sampling. Untuk menentukan calonresponden penulis menggunakan sampling jenuh. Teknik analisis data yang digunakanyaitu Analisis Deskriptif, Methode of successive Interval (MSI), Uji Normalitas, Analisis Regresi Sederhana, Uji t dan Koefisien Determinasi. Setelah dilakukanpenelitian terhadap masing-masingvariabel, responden memberikan tanggapanpositif bahwa film Penyalin Cahayamemiliki pengaruh yang signifikanterhadap tingkat kesadaran kekerasanseksual bahwa varians yang terjadi padaTingkat Kesadaran Kekerasan Seksualdikalangan mahasiswa Fikom Unisba 2018. (Y) sebesar 69,722% ditentukan oleh varianyang terjadi pada variabel pengaruh filmPenyalin Cahaya (X). Sebesar 30.278% ditentukan oleh faktor-faktor lain di luarpenelitian.